2003
DOI: 10.1046/j.1440-1797.2003.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteodystrophy in Indonesian haemodialysis patients

Abstract: A preliminary study of the intact-parathyroid hormone (i-PTH) measurements from haemodialysis patients was conducted to determine the prevalence of renal bone diseases at the Dr Soetomo Hospital. The objective of this study is to evaluate the osteodystrophy renal pattern in haemodialysis patients using i-PTH and radiological parameters. The selected populations of 48 (32 males and 16 females), the mean age 48 +/- 10.3 years, was evaluated to conduct a cross-sectional study. The calorimetric method was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…reported. [1819] Santoso et al . studied 48 Indonesian hemodialysis patients with iPTH and found a prevalence of 72%.…”
Section: Discussionmentioning
confidence: 99%
“…reported. [1819] Santoso et al . studied 48 Indonesian hemodialysis patients with iPTH and found a prevalence of 72%.…”
Section: Discussionmentioning
confidence: 99%
“…Also, low turn-over osteodystrophy in our study was less frequent than reported in Canada (9). This can be related to a younger age of our patients like in many developing countries where access to dialysis is generally limited to active adult population (10). Manifestations of CKD-MBD were unspecific and the majority of our patients were asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Manifestations of CKD-MBD were unspecific and the majority of our patients were asymptomatic. This lack of specificity of clinical symptoms had been emphasized by many authors and it makes diagnosis of CKD-MBD more difficult (10-12). In the study by Hercz et al, about two thirds of patients with aplastic osteopathy did not present any clinical symptom (9).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the nature of CKD and the result of an Indonesian study that reported hypocalcemia in 61% of patients. 18 The development of ROD begins too early during CKD. The three important pathogenic mechanisms include reduced calciferol production (glomerular filtration rate (GFR) < 90 mL/min/1.73 m 2 ), hyperphosphatemia (GFR < 35–30 mL/min/1.73 m 2 ), and hypocalcemia occurring relatively early during CKD.…”
Section: Discussionmentioning
confidence: 99%